Probiotics modulate the microbiota-gut-brain axis and improve memory deficits in aged SAMP8 mice - Xueqin Yang; Dongke Yu; Li Xue; Hui Li; Junrong Du (Elsevier, 2020)
ProBiotic-4 is a probiotic preparation composed of Bifidobacterium lactis, Lactobacillus casei, Bifidobacterium bifidum, and Lactobacillus acidophilus. This study aims to investigate the effects of ProBiotic-4 on the microbiota-gut-brain axis and cognitive deficits, and to explore the underlying molecular mechanism using senescence-accelerated mouse prone 8 (SAMP8) mice. ProBiotic-4 was orally administered to 9-month-old SAMP8 mice for 12 weeks. We observed that ProBiotic-4 significantly improved the memory deficits, cerebral neuronal and synaptic injuries, glial activation, and microbiota composition in the feces and brains of aged SAMP8 mice. ProBiotic-4 substantially attenuated aging-related disruption of the intestinal barrier and blood-brain barrier, decreased interleukin-6 and tumor necrosis factor-α at both mRNA and protein levels, reduced plasma and cerebral lipopolysaccharide (LPS) concentration, toll-like receptor 4 (TLR4) expression, and nuclear factor-κB (NF-κB) nuclear translocation in the brain. In addition, not only did ProBiotic-4 significantly decreased the levels of γ-H2AX, 8-hydroxydesoxyguanosine, and retinoic-acid-inducible gene-I (RIG-I), it also abrogated RIG-I multimerization in the brain. These findings suggest that targeting gut microbiota with probiotics may have a therapeutic potential for the deficits of the microbiota-gut-brain axis and cognitive function in aging, and that its mechanism is associated with inhibition of both TLR4-and RIG-I-mediated NF-κB signaling pathway and inflammatory responses. Key words: Microbiota-gut-brain axis, Cognitive decline, TLR4, RIG-I, NF-κB, Probiotics, SAMP8 mice